Diodorus Siculus as a Source for the Study of the Sicilian Servile Wars: ὠφέλεια, ἐπιείκεια and τυχή in his Narrative - Martín Piantanida, Fernando (Gerión. Revista de Historia Antigua, 2021)
In this article we address the question of the historical credibility of the Diodorean account of the Sicilian servile wars by reconsidering its author in the light of the contributions of the interpretative current that rehabilitates it. Taking a distance from the Quellenforschung, we study its narrative not as a direct derivation from its supposed source (Posidonius of Apamea), as modern historians have usually done, but putting it in relation to the Historical Library as a whole (its historical method, the themes and conceptions of history that give unity to the work). In this way, we configure the Diodorean account as a source in itself by analyzing it through three central concepts of the author's thought (the moral benefit for the reader, moderation and fortune) and we argue in favour of its usefulness as a historical source, because its didactic and moralistic purpose does not seem to be developed to the detriment of the events narrated.
Keywords: Diodoren Account; Historical Credibility; Method; Sicilian Servile Wars; Quellenforschung; Moderation; Pride; Benefit; Fortune